Differentiated Instruction: Integrating Content, Process, Product, and Learning Environment for Diverse Learners in English Language Teaching (ELT) - Tira Nur Fitria (Talenta Publisher, 2026)
This research explores and simulates the integration of differentiated instruction elements of content, process, product, and learning environment in English Language Teaching (ELT) to accommodate the diverse readiness levels, interests, and learning profiles of students. This study employs a descriptive qualitative method. The analysis shows that differentiated instruction in English Language Teaching (ELT) involves four key components: content, process, product, and learning environment. Differentiating content means adjusting what students learn based on their readiness, interests, and language levels while keeping learning objectives consistent. For example, students may study the same topic—like daily routines or food—but use materials of varying complexity, from simple visuals to analytical texts. Differentiating the process involves varying how students engage with content, using diverse strategies that suit visual, auditory, kinesthetic, or interpersonal learners. This might include activities like acting, using images, or role-playing. Differentiating the product means giving students choices in how they demonstrate their learning—through writing, drawing, presenting, or creating digital content—allowing them to use their strengths while meeting the same goals. Lastly, differentiating the learning environment focuses on modifying the physical, emotional, and social classroom setting to support all learners. This could involve flexible seating, sensory-friendly spaces, and inclusive practices that reduce anxiety and promote engagement. Overall, these components help ELT more inclusive, engaging, and responsive to the diverse needs of students.